Students’ Perceptions of the Use of Flashcards in Enhancing Vocabulary at MA Tarbiyatus Shibyan Sungai Kunyit Sekip II - Nur Azizah (International Journal of Social Sciences, 2025)
This study aims to explore students’ perceptions of the use of flashcards in enhancing students’ vocabulary at MA Tarbiyatus Sibyan Sungai Kunyit Hulu Sekip II. This research employed a qualitative descriptive design. The total of participants in these research were 21 students of class XI. Most of the students are famle. The data were collected through interviews, observations, and documentation. The finding of this research was revealed with the result of students’ interview. It showed that most of the students had positive perceptions toward the use of flashcards in learning process English, especially vocabulary. It can help the students to improve their vocabulary and make the students enjoy when they are learning English. Flashcards helped students memorize new words more easily, increased their motivation, students are able to develop a single word into a sentence, and made the learning process more enjoy. Therefore, flashcards can be considered an effective medium in improving students’ vocabulary acquisitio at MA Tarbiyatus Shibyan.